Symbolic Religious Landscape: Religious and Patriotic Symbolism in the Pilgrimage Centres in Poland - Justyna Liro; Izabela Sołjan; Elzbieta Bilska-Wodecka (Religions, 2022)
Combining religious and national symbolism is not a new phenomenon. There are known examples of countries where there were or still are connections between nationality and religion. Pilgrimage centres are examples of symbolic religious landscapes based on the presence of the sacred. Such anthropogenic landscapes are a visible result of culture formed under the influence of religion, a special spiritual and often national heritage expressed through sacred objects, visual evidence of religiousness and, likewise, national identity. Here, we present a detailed analysis of religious and patriotic symbolism present in the largest pilgrimage centres in Poland. Additionally, the paper discusses a. the historical and socio-cultural conditions of the presence and significance of these elements in religious landscapes; b. the strong relationships between religiousness and the sense of national identity, and c. the resulting significant importance of pilgrimage centres in the development and consolidation of a sense of national identity. Symbolic elements in the analysed pilgrimage centres refer to both universal religious content and cults popular in the Roman Catholic Church, as well as to the identity of the analysed places. In addition to religious symbolism, national and patriotic symbols often occur in Polish sanctuaries. Their occurrence is historically conditioned and, to a large extent, results from the strong ties between religiousness and national identity.